Orientalist Ambivalence: Translating the Qur'an in the Dutch Republic - van der Deijl, Lucas (Early Modern Low Countries, 2022)
This article compares the first two Dutch translations of the Qur’an printed in the Dutch Republic: De Arabische Alkoran (1641) published by Barent Adriaensz Berentsma and Mahomets Alkoran (1657) published by Jan Rieuwertsz. It builds upon previous bibliographic research by quantifying the abbreviation of the Surahs in the two editions, identifying the sources of the paratexts, and describing the different strategies for translation. This analysis reveals how different editing choices reflect contradictory ideological attitudes among the publishers and translators involved. These producers of the first Qur’an translations echoed the widespread hostility towards Islam in Western discourses while also highlighting the peaceful nature of Muhammad and the similarities between the Bible and the Qur’an. This ‘Orientalist ambivalence’ not only resonated in local debates about freedom of conscience among Amsterdam Mennonites, but also signalled a more fundamental epistemological uncertainty following the rise of Cartesianism in the Dutch Early Enlightenment.